Association between healthy eating index, body mass index, and early childhood caries in schoolchildren of Sakaka, KSA: A case-control study - Sudhakar Vundavalli; Anil Kumar Nagarajappa; Radhika Doppalapudi; Adel Saleh Alhabarti; Ahmed Saad Assaf Aleiadah; Mazen Nafa H. Alruwili (Wolters Kluwer Medknow Publications, 2019)
Background: Early childhood caries (ECC) was observed in children worldwide, and it adversely affects the oral health-related quality of life. ECC is multifactorial, and the concepts of poor nutrition and inappropriate feeding bottle habits as its risk factors could not provide sufficient evidence. Aim: The study aimed to assess the relation between Healthy Eating Index (HEI), body mass index (BMI), and ECC in the age group of 5-6 years children. Materials and Methods: A case-control study was carried out among 350 schoolchildren of Sakaka, KSA. Caries experience was recorded using decayed, missing, and filled teeth (dmft) index (WHO criteria 1997); various anthropometric measures such as weight, BMI, and height were recorded as per the standard guidelines. The Pearson's correlation coefficient and unpaired t-tests were used as bivariate tests; ANOVA with Tukey's post hoc for multivariate analysis. Results: A total of 350 male participants participated in the study, with the age range of 5-6 years and the mean age being 5.4 ± 0.7. The prevalence of ECC in the study population was 87%. The mean dmft values for each BMI category among the underweight, normal, overweight, and obese children were 4.73, 7.8, 9.4, and 10.8, respectively. The mean intake of grains was 1.9, vegetables 0.61, fruits 1.31; milk 1.78, meat/dal 4.8, total fat 9.9, saturated fat 9.9, cholesterol 10 refined carbohydrates 10, and variety 0.17 in children with severe ECC (S-ECC). Overall mean HEI score was significantly higher in children with S-ECC compared to simple ECC low (43.25 ± 3.44 vs. 57.46 ± 4.12), and HEI and dmft values were negatively correlated (−0.932). Conclusion: There is a negative relationship between ECC and HEI scores and positive correlation between BMI scores and ECC. Diet is again proved as a common risk factor for dental caries and obesity. Hence, the Nutritional Education Program is the need of an hour for these children and parents.